(untitled) (Altre Modernità, 2021)
In the years of the 2008 world financial crisis and of the global protests of the Occupy-Movement, the German author Ingo Schulze writes a novel about the German reunification, in which he tells the story of the ‘GDR-rogue’ Peter Holtz fighting for a fairer society. In this novel Schulze challenges the question of the democratic quality of the political and economic world order arisen at the historical moment of the Fall of the Berlin Wall. Why does Schulze decide to write just a picaresque novel about the German reunification during the financial crisis after 2007? What is the additional value of this literary elaboration of the historical turning point of 1989? Why does money play such a significant role in this novel? The contribution expounds that Schulze retrospectively and critically retraces in his picaresque novel the way from the ‘anti-fascist rampart’ of the GDR to the moneycentred financial world of Wall Street. The article illustrates at the same time Schulze’s diagnosis according to which during the process of German reunification the West betrayed its own democratic values and against the background of the peaceful revolution in the GDR missed the historical chance to build a fairer future society.